2014
DOI: 10.2522/ptj.20120432
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Exercise During Pregnancy Among Women Who Perform Regular Resistance Training: A Qualitative Study

Abstract: Pregnant women strived to exercise if the exercise facilitators outweighed the barriers. As the study described facilitators, barriers, and strategies for how to overcome exercise barriers, the results can be useful in exercise promotion in healthy pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 24 publications
4
25
0
5
Order By: Relevance
“…it is assumed that the investigated group perceived exercise as a valuable and necessary component of health even before pregnancy. this finding is similar to that observed in a group of 17 women who performed regular resistance training before becoming pregnant and continued during pregnancy [21]. the major motive for continuing resistance training during pregnancy was the expected benefits -to both mother and foetus.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…it is assumed that the investigated group perceived exercise as a valuable and necessary component of health even before pregnancy. this finding is similar to that observed in a group of 17 women who performed regular resistance training before becoming pregnant and continued during pregnancy [21]. the major motive for continuing resistance training during pregnancy was the expected benefits -to both mother and foetus.…”
Section: Resultssupporting
confidence: 88%
“…the major motive for continuing resistance training during pregnancy was the expected benefits -to both mother and foetus. All of the women stated that there were more health benefits than risks and some used exercise as motivation to avoid common pregnancy-related issues such as postural changes and back pain [21]. thus, while these women did not describe motives by each trimester, staying healthy was a top priority and corroborated the current findings.…”
Section: Resultssupporting
confidence: 81%
“…Four key themes were identified from the data which appeared to influence women's beliefs, intentions and behaviour. Although similar barriers have been found in previous research, (Cramp et al 2009, Leiferman et al 2011, Sui et al 2013, Reyes et al 2013, Fieril et al 2014, Redmond et al 2014, Denison et al 2015& Thompson et al, 2015. This study has focused on a combination of diet and physical activity to encourage a healthy lifestyle rather than one or the other.…”
Section: Discussionmentioning
confidence: 53%
“…34 Data collection methods used in the qualitative studies were focus groups in six studies, 29,39,40,45,47,51 interviews in seven studies 42,46,[48][49][50] and a combination of both methods was used in one study. 41 Only six studies assessed barriers in more than one time point during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…In our literature review, the studies conducted with previously active women had shown that although they reported similar barriers to LTPA during pregnancy, they usually show a desire to maintain their pre-pregnancy exercise routine during pregnancy. 43,48,49 In this context, the strategy of modifying and/or adapting usual activities is frequently used to overcome the perceived barriers to LTPA engagement during the gestational period. Similarly, many studies have found the intensity of perceived barriers to differ according pre-pregnancy levels of LTPA and that previous LTPA is one of the strongest predictors for maintaining LTPA during pregnancy.…”
Section: Discussionmentioning
confidence: 99%